A Method of Supporting Conflict Resolution for Designing Services - Akiyama, Y.; Shimomura, Y.; Arai, T. (Cranfield University Press, 2009)
Recently, the importance of service has been emphasized in various industries. However, few studies have focused on service design in spite of its great relevance. This paper proposes a methodology for service design, which enables designers to determine existing conflicts in design solutions and obtain basic strategies to solve them using computers. Two different approaches for detecting conflicts are proposed; one is the use of lexical expressions of functions, and the other involves the ranges of design parameters. At the end, the verification of the proposed methodology is carried out through application to an existing case.
Organised by: Cranfield University
Keywords: Service Engineering; Design Support; CAD